Precedents of the Satisfaction of Mobile Shoppers. a Cross-Country Analysis - Marinao-Artigas, E (Elsevier B.V., 2020)
This investigation into m-commerce suggests a model in which some experiential dimensions of online shopping act as antecedents of m-shopper satisfaction. Causal relationships are tested by a model of structural equations. A non-probabilistic convenience sample composed of mobile buyers from Chile and Mexico is used. The results show that the m-shopper s satisfaction with their online shopping experience is a consequence of the reputation and trust that they perceive of mobile commerce. In turn, it is confirmed that satisfaction is a reaction to the affective evaluation of the mobile shopper. Affective evaluation is understood as the result of the hedonic and functional attributes perceived by mobile shoppers in their online shopping experience. Among m-shoppers from Chile and Mexico, differences are observed in the relationships between reputation and trust and between functional benefit and affective evaluation. This study contains some implications for mobile commerce managers who want to improve mobile buyer satisfaction. © 2019 Elsevier B.V.